A Note on the Decision of a Sales Maximizer in Response to the Increase of Per Unit Cost - Yao, Shuntian (School of Management Working Papers, 1996)
In this paper the author compares the behaviors of a sales revenue maximizer with that of a profit maximizer in their response to an increase of the per unit production cost or a per unit tax being imposed, A mistake in a currently used textbook is pointed out, and a new proposition is proposed for replacing a false statement there.